2017
DOI: 10.1111/cch.12444
|View full text |Cite
|
Sign up to set email alerts
|

A study into the effectiveness of a postural care training programme aimed at improving knowledge, understanding and confidence in parents and school staff

Abstract: Results suggest improvement in knowledge, understanding and confidence in parents and school staff that care for children with significant physical postural care impairments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 20 publications
0
22
0
3
Order By: Relevance
“…Linked to this, we would note a recently completed NIHR study within the Research for Patient Benefit programme, which evaluated training school staff (and parents) in postural care. 47 In the remainder of this chapter, we return to the study objectives, reporting for each the key findings and broad conclusions that can be drawn. 1. to identify and describe current techniques, practices and approaches to delivering therapy interventions for children with non-progressive neurodisability that seek to improve participation as defined by the ICF 2. to describe therapeutic approaches identified by professionals as promising or innovative but not currently (routinely) delivered by the NHS.…”
Section: Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Linked to this, we would note a recently completed NIHR study within the Research for Patient Benefit programme, which evaluated training school staff (and parents) in postural care. 47 In the remainder of this chapter, we return to the study objectives, reporting for each the key findings and broad conclusions that can be drawn. 1. to identify and describe current techniques, practices and approaches to delivering therapy interventions for children with non-progressive neurodisability that seek to improve participation as defined by the ICF 2. to describe therapeutic approaches identified by professionals as promising or innovative but not currently (routinely) delivered by the NHS.…”
Section: Study Limitationsmentioning
confidence: 99%
“…[48][49][50][51] Notions of feeling overburdened by the requirements of a therapy regime, and a lack of ongoing training and support, have also been reported. 52 In terms of work within the existing NIHR portfolio, a study 47 funded as part of the Research for Patient Benefit programme has been recently published, which evaluated a training intervention for parents and school staff on postural management. Different models for organising therapy provision were reported, and alternatives to the traditional model of 'unitherapy' teams were presented.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Providing support and training is an integral and fundamental element of 24-hour postural management (Castles et al, 2014;Hotham et al, 2017;Humphreys and Pountney, 2006;Maher et al, 2011), and the current survey found that this was the area wherein occupational therapists felt most skilled. In contrast, the service users and carers found that the training and support they received was inadequate, especially lack of support for night-time positioning.…”
Section: Discussionmentioning
confidence: 78%
“…This is the first study to examine both carers’ and service users’ experiences of 24-hour postural management as a whole using focus group methodology. Previous studies have addressed certain elements, such as standing frames, and have focused solely on conditions such as cerebral palsy (Goodwin et al., 2018a, 2018b, 2019), while others have addressed the views of parents, teachers and therapists (Hotham et al., 2017; Hutton and Coxon, 2011; McDonald et al., 2007; Maher et al., 2011; Nicolson et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation